Hybridization of potential germplasm to create genetic variation for identification of superior cross combinations in bread wheat (Triticum aestivum) - CHAUDHARY, NIRDESH KUMAR; GANGWAR, LOKESH KUMAR; MOHAN, SHIVA; KUMAR, RAJ; KUMAR, VIVEK; EDHIGALLA, PREMNATH (The Indian Journal of Agricultural Sciences, 2025)
A systematic hybridization was made for inducing genetic variation to produce high yielding genotypes with a high degree of heterosis and combining ability. The present study was carried out at during winter (rabi) season 2020–21 and 2021–22 at Crop Research Centre, Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut, Uttar Pradesh to identify superior genotypes with strong general combining ability (GCA) and crosses with the potential to significantly enhance wheat (Triticum aestivum L.) yields in the future. The experiment was conducted with 10 parents to produce 45 hybrids using half diallele mating design, while evaluation of the same 10 parents and 45 hybrids using randomized complete block design (RCBD) with 3 replications, grown under normal conditions. Analysis of variance revealed that both sources of variation i.e. GCA and specific combining ability (SCA), were significant with regard to all the studied traits. Boxplot revealed that hybridization creates sufficient genetic variation for all the traits. Based on the magnitude of GCA effects, genotypes NW 5054, UP 262, and HD 2285 have been observed as significant combiners for the trait grain yield/plant. Estimates of SCA and per se performance, cross K 9162 × WR 544 followed by UP 262 × HD 3086, UP 262 × WR 544, HD 2285 × PBW 226, and DBW 187 × NW 5054, were the best significant specific combiners for grain yield/plant. The best heterosis crosses were UP 262 × HD 3086, K 9162 × WR 544, UP 262 × HD 2285, UP 262 × WR 544, HD 2285 × PBW 226, and DBW 187 × NW 5054, which exhibited superior heterosis over both better and mid parents for grain yield per plant. These parents and hybrids can be used further for crop improvement.